Clinical characteristics and surgical outcome of pediatric and early adulthood retinal detachment. Issue 3 (May 2021) - Eibenberger, Katharina; Sacu, Stefan; Rezar-Dreindl, Sandra; Schmidt-Erfurth, Ursula; Stifter, Eva; Georgopoulos, Michael
Objective: The aim of this study was to evaluate and compare the underlying pathologies, demographic and retinal detachment characteristics in pediatric and early adulthood retinal detachment. Methods: Patients with rhegmatogenous, serous, or tractional retinal detachment aged 0–26 years were retrospectively reviewed. The preschool group (n = 4) comprised children aged 0–6 years, the pediatric group (n = 19) comprised children aged 7–16 years, and the early adulthood group (n = 13) aged 17–26 years. Demographic information and retinal detachment characteristics, type of surgery, and intraocular tamponade were analyzed. Postoperatively, the functional outcome, anatomic success, and ocular adverse events were evaluated. Due to the low patient number in the preschool group, statistical analysis was performed for pediatric group and early adulthood group only. Results: All causes of retinal detachment were present in the pediatric group, but only rhegmatogenous retinal detachment in the early adulthood group. In both groups, the main type of surgical intervention was pars plana vitrectomy (pediatric group: 52%, early adulthood group: 38%; p = 0.36). The type of intraocular tamponade varied statistically significantly between the groups (p = 0.014). Silicone oil was the main intraocular tamponade in the pediatric group (48%), whereas no tamponade (54%) followed by gas tamponade (46%) in the early adulthood group. Final attachment rate was similar in both groups (pediatric group: 89%, early adulthood group: 100%; p = 0.35). Re-detachment occurred significantly sooner in the pediatric group (1.3 ± 0.3 months) than in the early adulthood group (4.3 ± 1.4 months; p = 0.03). Conclusion: In pediatric and early adulthood retinal detachment, pars plana vitrectomy appeared as a successful surgical intervention. Re-attachment rate and re-treatment were similar in both groups with a better functional outcome observed in cases of retinal detachment in early adulthood and poorer results in young children.